Magnetic attachments for dentures

The magnetic attachment for dentures addresses the challenge of maintaining strong adsorption force and preventing falling off by using a composite magnet with a flange-guided flux flow and non-magnetic shield, achieving enhanced durability and adsorption.

JP7606718B1Active Publication Date: 2024-12-26MAGNE DESIGN
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024137473
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-06-05
Filing Date
2024-08-17
Publication Date
2024-12-26
Estimated Expiration
2044-08-17

AI Technical Summary

Technical Problem

Conventional magnetic attachments for dentures face challenges in achieving strong adsorption force while maintaining a compact size, as measures to prevent falling off often disrupt magnetic flux flow, reduce suction force, or increase the attachment's size, leading to potential breakage.

Method used

A magnetic attachment design featuring a composite magnet with a flange portion that guides magnetic flux flow smoothly through an R-shaped inclined surface and a fibrous structure, combined with a non-magnetic shield plate and a metal adhesive coating on a thorn-like uneven surface, ensuring high adsorption force and preventing falling off.

Benefits of technology

The design achieves a magnetic attachment with a strong adsorption force up to 1.4 times higher than conventional products, effectively preventing detachment while maintaining a compact size and ensuring durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606718000001_ABST
    Figure 0007606718000001_ABST
Patent Text Reader

Abstract

It consists of welded parts with excellent resistance to falling off, high magnetic attraction, sufficient magnetic blocking properties and excellent weld strength, and also simplifies the manufacturing process. [Solution] A flange consisting of protrusions is provided on a cap 1 made of Cr-based magnetic stainless steel that houses a permanent magnet 2 by a combination of backward extrusion press processing and forward extrusion press processing through cold working, and a metal adhesive is applied to the spiky uneven surface on the outer surface excluding the attraction surface of the magnetic structure and cured, and a shield plate 3 that covers the opening of the recess in the cap 1 is made of an 18Cr-8Ni stainless steel magnet except for the outer periphery 31, and its outer periphery 32 is made of a nonmagnetic part of 18Cr-8Ni stainless steel that has been nonmagnetically modified, and a weld is formed by laser welding at the boundary between the cap 1 and the outer periphery 32 consisting of the nonmagnetic part of the shield plate 3. A keeper 102 is made of Cr-based soft magnetic stainless steel.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a magnetic attachment for dentures that can maintain and fix dentures by utilizing a strong magnetic attraction force in the dental field. [Background technology]

[0002] In recent years, dentures have begun to be manufactured using a 3D printer based on the digital data of the design, after the state of the teeth in the oral cavity has been diagnosed using X-ray image analysis equipment and 3D shape measurement. In other words, dentures are changing from precision cast dentures to digital dentures. Magnetic attachments for magnetic dentures have been used as retention devices that are gentle on the teeth in precision cast dentures, but in the production of digital dentures, they are expected to utilize the self-attracting force of magnets to accurately and stably hold dentures to the abutment teeth. To achieve this, there is a demand for increased attractive force.

[0003] Conventionally, examples of magnetic attachments for dentures that utilize magnetic attraction are shown in Figures 11 and 12 disclosed in Patent Document 1. According to Figure 11, in order to attach a denture 50, a root plate 62 is embedded in a root portion 61 of a human tooth, and a keeper 6 is embedded in the root plate 62. The denture 50 is composed of a magnetic attachment for dentures 5 arranged to face the keeper 6, a resin base 63 that encases it, and an artificial tooth 64 made of enamel.

[0004] This device is required to be as small as possible and have a strong adhesive force. However, a problem arises that a smaller magnetic attachment 5 for dentures with a stronger adhesive force is that it is easy to come off from the resin base 63. The following inventions have been disclosed: Patent Document 2 proposes a magnetic attachment having a drum-shaped outer periphery, as shown in FIG. 13, which improves the attractive force and has a high resistance to falling off. Patent Document 3 proposes attaching a flange to the side of the cap as shown in FIG. Patent document 4 proposes a manufacturing process that improves the adhesion of a magnetic structure embedded in a denture using a magnetic structure with a resin layer made of adhesive resin, and reduces the manual work required by dentists and others to prevent the magnetic structure from falling off.

[0005] However, although the drum-shaped magnetic attachment of Patent Document 2 improves the ability to prevent falling off, the drum portion is large, which goes against the goal of miniaturization. The measure of attaching a flange in Patent Document 3 is effective in preventing the cap from falling off, but the flange is attached too high in the outer circumferential direction of the top surface of the cap, which reduces the adhesive force. Similarly, the measure of making a notch on the side of the cap also has the problem of reducing the adhesive force. The solution in Patent Document 4 involves rough polishing using barrel polishing, so the unevenness on the cap surface is smoothed out before the adhesive resin is applied, and therefore adhesion is not sufficiently improved. In addition, the method in which dentists sandblasted the surface of the cap and then applied the metal adhesive with a brush was a measure that was prone to quality variation and left some users with concerns about quality. Furthermore, in Patent Document 5, as shown in FIG. 2, a stainless steel magnet is used for the shield plate, which increases the strength of the residual magnetism to 800 to 1000 gf, making it possible to achieve an attractive force that is 1.4 times stronger than that of conventional products. Therefore, there has been a demand for measures to prevent the device from falling off while being compact and capable of dealing with strong suction power. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 4-227253 [Patent Document 2] Japanese Patent Application Publication No. 10-127664 [Patent Document 3] JP 2011-224109 A [Patent Document 4] JP 2001-112791 A [Patent Document 5] Patent No. 7125684 Summary of the Invention [Problem to be solved by the invention]

[0007] A conventional measure to prevent the cap from falling off is to provide a flange (also called a brim) or a notch by cutting the side of the cap. However, when trying to provide sufficient fall-off prevention with notches, there is a drawback in that the magnetic flux flow inside the cap is disturbed, reducing the adhesive force, as shown in Figure 3. Also, considering the relationship between the resin in the resin bed and the resin inside the notch, the fall-off prevention force is lower than with the next projection method. The larger the projection (flange) is, the more effective it is, but increasing the maximum diameter of the attachment makes it difficult to embed it in the denture and makes the denture more susceptible to damage. As for the location of the projection, if the length below the projection becomes too short, the anti-fall-off function weakens, so conventionally the projection was placed on the top surface of the attachment. However, this had the drawback of disrupting the flow of magnetic flux, as shown in Figure 4, and generating a magnetic vortex at the base of the projection, which reduces the adhesive force. An object of the present invention is to provide a flanged magnetic attachment for dentures that has an anti-fall-off function and suppresses a decrease in adhesive force. The present inventors have disclosed an invention in Japanese Patent No. 7125684 which comprises a welded portion having high attractive force, sufficient magnetic shielding properties and excellent weld strength, and which also simplifies the process. The present application is an improvement of that invention and solves the problems of the present invention by reference thereto. [Means for solving the problem]

[0008] The present inventors have thoroughly investigated the shape, position and size of the flange portion that does not disturb the flow of magnetic flux from the composite magnet in a magnetic structure that generates a strong attractive force, and have also investigated a manufacturing method thereof. The flow of magnetic flux can be rectified without disturbances such as the generation of magnetic flux vortices by making it the flow shown in Figure 5. The magnetic flux from the composite magnet consisting of a permanent magnet and a stainless steel magnet flows diffusely from the center to the periphery at the top of the cap (corresponding to the bottom of the cap), and flows from the top to the bottom on the side of the cap. The magnetic flux that has flowed to the periphery is received by the curved surface at the top of the side of the cap, and the flow is rectified smoothly, thereby preventing vortexes and disturbances that occur inside the flange. The means for this is to guide the flow of magnetic flux by using an inclined surface at the upper end of the cap that slopes outward in an R-shape. Furthermore, by making the material structure of the flange portion having the inclined surface at the upper end of the cap that slopes outward in an R-shape into a smooth fibrous structure, magnetic flux can flow along the fibrous structure. In other words, the cross section of the outer periphery of the flange is fan-shaped, with the R-shape of the fan being made up of fibrous tissue that is about 1 / 4 of the annual rings, and from the bottom of the flange to the side of the cap is a small inverted R-shaped fibrous tissue.

[0009] Regarding the position of the flange, the upper end of the flange extends outward from the upper end of the cap and gradually declines in an inclined plane. The lower end (bottom surface) of the flange is at approximately the same position as the inner bottom surface of the cap in Figure 5, and the lower end is flat. Next, the width of the flange, in other words the protrusion from the side of the cap, is preferably 0.1 mm to 0.25 mm. If the protrusion is less than 0.1 mm, the fall-off prevention force cannot be secured. Conversely, if it exceeds 0.25 mm, the fall-off prevention force is improved, but the attachment cannot be made smaller.

[0010] Furthermore, in order to achieve a magnetic adhesion force of 1000 gf when combining a permanent magnet and a stainless steel magnet, as shown in Figure 2, the team came up with the idea of ​​making the surface of the magnetic structure a spiky, uneven surface with triangular pyramidal peaks of approximately the same depth and width, and then applying a strong metal adhesive with a thickness of 20 μm or less onto this uneven surface and then curing it. Effect of the Invention

[0011] The present invention provides a strong anti-fall function to the magnetic attachment for dentures, which is realized by a composite magnet consisting of a permanent magnet and a Cr-Ni stainless steel magnet used in the shield plate, making it possible to fully utilize the merits of the high attractive force. It also simplifies the manufacturing method and makes it possible to increase the strength of the welded parts. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a cross-sectional view of a magnetic attachment for a denture. [Diagram 2] FIG. 1 is a graph showing the relationship between the magnetic adsorptive force and the residual magnetism of a Cr-Ni stainless steel magnet. [Diagram 3] FIG. 13 is a diagram showing disturbance of magnetic flux during cutting (machining). [Figure 4] FIG. 13 shows the disturbance of magnetic flux in a flange (machined). [Diagram 5] FIG. 13 is a diagram showing the flow of rectified magnetic flux in a flange (cold worked) having an inclined surface with an R shape. [Figure 6] FIG. 1 shows (a) a protrusion formed by backward extrusion press processing and a fibrous structure that follows the shape of the protrusion, (b) a flange formed by forward extrusion press processing and its fibrous structure, and (c) a crack in the corner of the bottom surface of the cap caused by excessive forward extrusion press processing. [Figure 7] FIG. [Figure 8] 4A and 4B are diagrams showing an example of a welded portion of a magnetic structure. [Figure 9] 11A and 11B are diagrams showing other examples of the welded parts of the magnet structure. [Figure 10] 1 is a SEM photograph of the surface of a magnet structure that has been given a spiky, uneven surface by shot blasting. [Figure 11] FIG. 1 is a diagram illustrating a denture according to a conventional example. [Figure 12] FIG. 1 is a diagram showing a cross section of a magnetic attachment for dentures in a conventional example. [Figure 13]FIG. 1 is a diagram showing a cross section of a drum-shaped magnetic attachment for dentures in a conventional example. [Figure 14] FIG. 1 is a cross-sectional view of a conventional flanged magnetic attachment for dentures. BEST MODE FOR CARRYING OUT THEINVENTION

[0013] A first embodiment of the present invention is as follows. The magnetic attachment for dentures of the present invention comprises: A magnetic attachment for dentures comprising a magnetic structure to be placed on a denture and a keeper made of a soft magnetic material to be placed on an abutment tooth, the magnetic structure and the keeper being configured so that an attracting surface of the magnetic structure and an attractable surface of the keeper are brought into contact with each other by self-attraction caused by magnetic force, the magnetic structure has a cup-like shape with an opening, and its bottom and side portions are made of a cap made of Cr-based magnetic stainless steel, a permanent magnet housed in a recess of the cap, and a shield plate that covers the opening of the cap; The magnetic structure has a cylindrical shape with a diameter of 1.5 to 5 mm and a height of 0.8 to 2 mm. The permanent magnet is formed in a disk shape having a maximum energy product of 45 MGOe to 55 MGOe, a coercive force of 10 kOe to 20 kOe, a thickness of 0.5 mm to 1.6 mm, and an outer diameter of 1.2 mm to 4.6 mm. the cap has a flange portion consisting of a protrusion of 0.1 mm to 0.25 mm on a side surface of an upper end side not in contact with the keeper, the side surface portion having a parallel fibrous structure along the side surface and a hardness of Hv220 to Hv300; The flange portion has an R-shaped inclined surface that slopes downward toward the upper end of the cap and is made of a semicircular arc-shaped fiber structure. the shield plate has an outer periphery made of non-magnetic Cr-Ni stainless steel, and the other part of the shield plate is made of a Cr-Ni stainless steel magnet having a fibrous structure in the thickness direction; The Cr-Ni stainless steel magnet has magnetic properties in a saturated magnetized state of 8,000 G to 12,000 G of saturation magnetization, 100 Oe to 200 Oe of coercive force, 800 G or more of anisotropic magnetic field, and 6,000 G to 10,000 G of residual magnetism, a boundary between the outermost end of the cap side portion and the shield plate is joined by welding, and the suction surface including the welded portion is smoothed; The keeper is characterized in that it is disk-shaped, made of Cr-based soft magnetic stainless steel, and has a smoothed attraction surface. This makes it possible to obtain a magnetic attachment for a magnetic denture having a high magnetic attraction force and to prevent the magnetic attachment from falling off the denture.

[0014] The outer peripheral side surface of the cap is characterized in that it has a metal adhesive coating of 20 μm or less in thickness on a spiky uneven surface consisting of triangular pyramidal peaks with approximately the same depth and width. This makes it possible to prevent the magnetic attachment for dentures, which has a higher magnetic attraction force, from falling off.

[0015] A second embodiment of the present invention is as follows. The method for producing the magnetic structure of the magnetic attachment for dentures of the present invention includes the steps of: (1) First, in the manufacture of the three components that make up the magnet structure, the cap with a flange on the upper side made of Cr-based magnetic stainless steel, the permanent magnet made of a disk-shaped rare earth sintered magnet, and the shield plate, which is the base material for the disk-shaped stainless steel magnet, Step a) The cap is made by punching a Cr-based magnetic stainless steel plate as a base material into a disk shape by cold working; Step b) Next, a cap is formed by backward extrusion press processing, and a protrusion of 0.1 mm to 0.25 mm is protruded from the side surface of the upper end of the cap, and a fibrous structure is formed along the shape of the protrusion, with an R-shaped inclined surface being processed outward on the upper end of the cap, Step c) further comprises flattening a lower surface of the protrusion to form a flange portion by forward extrusion press processing, the flange portion having a semicircular arc-shaped fiber structure; In addition, by performing the backward extrusion press process and the forward extrusion press process, the side surface of the cap is made of a parallel fibrous structure along the side surface, The hardness is Hv220 to Hv300. Step d) the shield plate is made of a Cr-Ni non-magnetic stainless steel as a base material, which is cold drawn by 50% or more, and induced transformation of 80% or more of the austenite structure to martensite is performed. The base material is then cut into rings by machining to form a disk-shaped shield plate having a thickness of 0.1 mm to 0.2 mm and an outer diameter of 1.2 mm to 4.6 mm. The outer periphery of the shield plate is laser heated to be non-magnetically modified back to the Cr-Ni non-magnetic stainless steel consisting of the austenite phase, thereby forming a composite shield plate in which the center of the disk is made of stainless steel magnetic material and the outer periphery is non-magnetic. Step e) forming the permanent magnet into a disk shape having a maximum energy product of 45 MGOe to 55 MGOe, a coercive force of 10 KOe to 20 KOe, a thickness of 0.5 mm to 1.6 mm, and an outer diameter of 1.2 mm to 4.6 mm; (2) Next, in assembling the magnetic structure consisting of the three parts of the cap, the composite shield plate, and the permanent magnet, Step f) inserting the permanent magnet into the hole of the cap, covering it with the composite shield plate, and assembling the three parts; Step g) welding the boundary between the cap and the shield plate; (3) Then, in the surface treatment, magnetization and inspection of the assembled magnetic structure, Step h) shot blasting the magnet structure, applying a metal adhesive thereto, and curing the same; Step i) polishing the attraction surface of the magnetic structure to make it smooth; Step j) applying a magnetic field of 2 T or more in a height direction to magnetize the magnetic structure; Step k) inspecting the attraction between the magnet structure and the keeper; The present invention is characterized by comprising the steps of: This makes it possible to simplify the process while maintaining the anti-falloff function by changing from the conventional cutting process to press processing.

[0016] In step d), the outer periphery of the shield plate may be made non-magnetic by high-frequency heating. Furthermore, in step d), only the formation of the shield plate may be performed, and in (2), the shield plate, cap, and permanent magnet may be assembled, and the outer periphery of the shield plate may be demagnetized by the laser welding heat at the same time as laser welding the boundary between the cap and the shield plate. This laser welding non-magnetic modification technology simplifies the process by eliminating the need for laser heating or high-frequency heating to form the composite shield plate.

[0017] The magnetic attachment for a denture and the method for manufacturing the magnetic attachment for a denture will be described with reference to Figs. As shown in Fig. 1, the denture magnetic attachment 10 is composed of a magnetic structure 101 and a keeper 102. The magnetic structure 101 is disposed on the denture base 63 and exerts a magnetic attraction force. On the other hand, the keeper is made of a soft magnetic material and disposed on the abutment. The relationship between the two is such that an attracting surface is provided on the magnetic structure on the one hand, and an attracted surface is provided on the keeper on the other hand, and the two are configured so that when the attracting surface and the attracted surface are brought into contact with each other, they are attracted to each other by the magnetic attraction force. Furthermore, in order to prevent the magnetic structure 5 from falling off the denture base 63 due to the magnetic attraction force between the two, as shown in Figure 11, the magnetic structure 5 is shaped to have a flange 11 consisting of a protrusion on the magnetic structure 101, and a metal adhesive is applied to the uneven surface formed by shot blasting on the surfaces of the magnetic structure 101 other than the attraction surface, and then cured. The details will be explained below.

[0018] <Magnet structure 101> The magnetic structure 101 is composed of a permanent magnet 2, a cap 1 with a flange 11 for accommodating the permanent magnet 2, and a shield plate 3 for covering the opening of the cap. The size of the denture is a cylinder with a diameter of 1.5 mm to 5 mm and a height of 0.8 mm to 2 mm. These dimensions are compatible with the shape of the artificial tooth. If it is too large, the denture will be easily cracked, and if it is too small, sufficient adhesive force will not be obtained.

[0019] <Cap 1> The Cr-based magnetic stainless steel cap 1 is produced by cold working a soft magnetic Cr stainless steel plate such as 18Cr stainless steel or 18Cr-2Mo stainless steel as the base material. It is punched into a disk shape, and then a combination of backward and forward extrusion press processes is used to produce a cylindrical container having a flange 11 with a flange width of 0.1 to 0.25 mm on the upper side surface that does not come into contact with the keeper.

[0020] Figure 6 shows (a) the protrusion formed by backward extrusion press processing and the fibrous structure following the shape of the protrusion, (b) the flange formed by forward extrusion press processing and its fibrous structure, and (c) cracks in the corners of the cap surface caused by excessive forward extrusion press processing. The backward extrusion press process forms a cap, and the material protrudes from the side of the upper end of the cap to form a protrusion, forming a fibrous structure that conforms to the shape of the protrusion. This provides hardness and magnetic adhesion, but the lower surface of the protrusion has a smooth R-shape, so although it has a protrusion, it does not provide sufficient anti-falling functionality. To address this issue, a forward extrusion press process is added to flatten the underside of the protrusion, completing the flange portion.

[0021] The position of the flange portion 11 is such that its upper surface is almost the same as the upper end surface of the cap, and its lower surface is at a position equivalent to the thickness from the upper surface to the upper part of cap 1. If the flange portion 11 is pressed too hard during the forward extrusion press processing and becomes thinner than the thickness of the upper part of cap 1, cracks are likely to occur in the corners of the bottom surface of the cap, as shown in Fig. 6(c). The flange portion 11 has an R-shaped inclined surface that slopes down outward on the upper end surface of the cap 1, and its internal structure is made of a semicircular fiber structure. The lower surface of the flange becomes flat from the end of the R-shaped inclined surface and wraps around into a small R shape toward the cylindrical side surface.

[0022] The hardness of the container produced by cold working is hardened to Hv220 to Hv300 due to the fibrous structure. If the hardness is less than Hv220, the polishing resistance of the portion (ring) constituting the adsorption surface at the very end of the side portion of the cap 1 and the wear resistance of the adsorption surface after polishing are insufficient. Furthermore, if the hardness of that portion is too soft compared to the hardness of the martensitic structure of the shield plate, which is Hv350, the outer periphery of that portion (ring) will sag during polishing, making it difficult to form a flat adsorption surface, which is also one factor in reducing the magnetic adsorption force. Preferably, the hardness is Hv260 to Hv280. Its magnetic properties are preferably a coercive force Hc of 50 Oe or less and a Bs of 1.3 T or more, which allows a sufficient magnetic attraction force to be obtained.

[0023] The flange portion 11 is work-hardened to Hv 250 to 300. If the hardness is less than Hv 220, the magnetic structure 101 is not sufficiently prevented from falling off from the denture base, and if the hardness exceeds Hv 300, the magnetic attraction force decreases. Furthermore, the semicircular fiber structure contributes to rectifying the flow of magnetic flux from the composite magnet in the flange portion 11 which is prone to causing turbulence within the cap 1 as shown in FIG. The side surface of the cap 1 is made of parallel fibrous tissue along the side surface, which facilitates the flow of magnetic flux.

[0024] <Permanent magnet 2> The permanent magnet 2 is preferably a rare earth magnet such as an Nd-Fe-B magnet (NdFeB magnet). In the NdFeB magnet, the larger the maximum energy product BHmax, the more preferable it is, so BHmax is set to 45 MGOe to 55 MGOe. With a maximum energy product of less than 45 MGOe, sufficient magnetic adsorption force cannot be obtained. Considering the upper limit of general-purpose NdFeB magnets, BHmax is set to 55 MGOe. The coercive force iHc is preferably as large as possible, but if it is too large, magnetization becomes difficult. The coercive force iHc is set to 10 kOe to 20 kOe. The size of the permanent magnet housed in the cap 1 is in the shape of a disc with a thickness of 0.5 mm to 1.6 mm and an outer diameter of 1.2 mm to 4.6 mm.

[0025] <Shield plate 3> The shield plate 3 is in the shape of a disc. The outer peripheral part is non-magnetic 32, and the part other than the outer peripheral part is made of a Cr-Ni-based stainless steel magnet 31. The Cr-Ni-based stainless steel magnet has a fibrous structure in the thickness direction and is magnetized in that direction. Its performance is such that the saturation magnetization is 8,000 G or more, the coercive force is 100 Oe to 200 Oe, the anisotropic magnetic field is 800 G or more, and the residual magnetism is 6,000 G or more. In particular, the larger the residual magnetism, the more the magnetic adsorption force increases as shown in Figure 2, so it is important to ensure 6,000 G or more. A composite magnet composed of the Cr-Ni-based stainless steel magnet 31 and the permanent magnet 2 housed in the cap 1 is formed to realize a large magnetic adsorption force. At the same time, the shield plate 3 welds the boundary part with the cap to protect the permanent magnet 2 from saliva in the oral cavity and corrosion. Furthermore, the non-magnetic part of the shield plate 3 magnetically blocks the composite magnet and the cap, preventing a decrease in the magnetic adsorption force.

[0026] <Manufacturing method of Cr-Ni-based stainless steel magnet> First, as shown in Fig. 7(A), the method for manufacturing a Cr-Ni stainless steel plate magnet involves cold drawing a Cr-Ni stainless steel bar in the austenitic phase by 50% or more to cause 60% or more of martensitic transformation, and then slicing it to produce shield plate 311 with a fibrous structure in the thickness direction. The size of this shield plate 311 is 0.1mm to 0.2mm in thickness and 1.2mm to 4.6mm in outer diameter. Next, the outer periphery of the shield plate 311 made of the semi-hard magnetic material in the martensitic transformation state is laser-heated to perform non-magnetic modification to return it to the austenitic phase Cr-Ni stainless steel 32. The width is 0.15mm to 0.3mm, and the thickness is the same as that of the shield plate, specifically 0.05mm to 0.20mm. This produces a composite shield plate 312, the center of which is made of the semi-hard magnetic material and the outer periphery of which is made of the non-magnetic material (non-magnetic part) (Figure 7(B)). The outer periphery of the shield plate 311 may be heated by high frequency heating. The shield plate 311 and the composite shield plate 312 are magnetized by applying a magnetic field of 3,000 Oe to 4,000 Oe in the thickness direction of the disks using an electromagnet to form permanent magnets. The composite shield plate 312 and the NdFeB magnet 2 may be stacked and pulse-magnetized together. The method for manufacturing the plate magnet is not limited to the above method, as long as the method can ensure a residual magnetism of 6,000 G or more.

[0027] <Assembly of the magnetic structure 101> A permanent magnet 2 is inserted into a cap 1 made of Cr-based magnetic stainless steel, and a composite shield plate 312 made of Cr-Ni-based non-magnetic stainless steel 32 and Cr-Ni-based semi-hard magnetic stainless steel 311 as a lid is pressed into the opening of the cap 1 to assemble the magnetic structure.

[0028] Next, the outer surface side of the boundary (joint) between the very end of the side part of the Cr-based magnetic stainless steel cap 1 and the ring-shaped Cr-Ni-based stainless steel 32 of the composite shield plate 312 is laser welded. As shown in Fig. 8, the weld 33 formed by laser welding is an alloy in which the Cr-based magnetic stainless steel 1 and the Cr-Ni-based stainless steel 32 are melted together, and a small amount of δ-ferrite phase precipitates, so it is necessary to ensure that the width of the nonmagnetic part 32 is of sufficient length so that the weld does not reach the inside of the nonmagnetically modified part. As a result, magnetic blocking can be achieved completely. In this method, the only conditions required for laser welding are those required to ensure joint strength. The boundary between the non-magnetic portion 32 and the Cr-Ni stainless steel magnet 31 is a straight line on the left and right. The size of the welded portion 33 is 0.1 mm to 0.25 mm in width (0.05 mm to 0.125 mm on the shield plate side), and the depth is 50% to 90% of the thickness with the shield plate.

[0029] Furthermore, a permanent magnet 12 is inserted into a cap 11 made of Cr-based magnetic stainless steel, and a shield plate 131 made of Cr-Ni-based semi-hard magnetic stainless steel is press-fitted into the opening of the cap 11 as a lid to assemble the magnetic structure.

[0030] Next, the outermost edge of the side portion of the Cr-based magnetic stainless steel cap 11 is laser welded to the surface side of the boundary (joint) between the Cr-Ni-based semi-hard magnetic stainless steel of the shield plate 131. When a composite shield plate is not used, as shown in Fig. 9, the boundary is joined by laser welding and at the same time, a heat-affected zone 131b caused by the welding heat is demagnetized on the outer periphery of the shield plate 131 side of the weld solidified zone 131a. The boundary between the magnetic material and the non-magnetic modified portion is affected by the rounding of the solidified portion 131a by welding, and a rounded heat-affected portion (non-magnetic portion) 131b is formed. The solidified portion 131a is an alloy in which Cr-based magnetic stainless steel 1 and Cr-Ni-based stainless steel are melted together, and the δ-ferrite phase is precipitated, but the magnetic shielding is completely achieved by the non-magnetic portion 131b formed in the surrounding heat-affected portion. The conditions for laser welding are those that ensure the joint strength, form a non-magnetic part due to the welding heat, and avoid thermal damage to the internal magnet due to welding heat transfer (i.e., deterioration of magnetic properties). By adjusting the amount of heat from the laser welding, it is possible to simultaneously form the joint and the non-magnetic part. Specifically, the weld penetration depth is expanded to the full thickness of the shield plate without damaging the internal magnet, thereby maximizing the heat-affected zone. The size of the welded portion 131a is 0.1 mm to 0.25 mm in width and 90% to 100% in depth of the thickness of the shield plate.

[0031] <Surface treatment and inspection of magnet structure> The outer peripheral surface of the cap of the magnetic structure is shot blasted with alumina powder of 50 to 100 μm in size. The crushed particles on the surface of the alumina powder form a spiky uneven surface with triangular pyramidal peaks of approximately equal depth and width on the outer peripheral surface, as shown in Figure 10. A metal adhesive is applied to this uneven surface and cured. The Cr-based magnetic stainless steel cap 1, which has a spiky, uneven surface, and the metal adhesive are intricately intertwined to form a strong bond, which in turn creates a strong adhesive force between this metal adhesive and the denture base resin, further improving the resistance to falling off. The thickness of the metal adhesive is 10 to 20 μm. A thickness of at least 10 μm is necessary to cover the depth of the spiky unevenness, and a thickness exceeding 20 μm is not preferable in terms of productivity, such as the amount of application, application time, and curing time.

[0032] The attracting surface of the magnetic structure 101 which comes into contact with the keeper 102 is a flat surface. After the above surface treatment, the attracting surface including the welded portion of the magnetic structure is polished to a flat surface. The cap formed by cold working had a fibrous structure and, due to work hardening, the hardness of the flange was Hv280. In addition, the hardness of the cap end surface (the ring that becomes the adsorption surface) was Hv270, and it had good abrasion resistance, with no grinding of the outer circumference of the ring.

[0033] <Creating Keeper 102> The keeper 102 is made by punching out a Cr-based soft magnetic stainless steel plate into a disk shape of a specified size. The attracted surface is also polished to a flat surface. Note that there are various shapes of keepers, including root keepers, but the upper surface of each is the attracted surface to the magnetic structure. If the hardness of the attracted surface of the keeper is lower than that of the magnet structure, the Cr-based soft magnetic stainless steel plate may be hardened by cold working before punching. Also, a Cr diffusion layer having a thickness of 3 to 8 μm may be formed on the attracted surface of the keeper to harden it. This improves the wear resistance of the keeper and extends its lifespan.

[0034] <Magnetization of magnetic structure> The permanent magnet 2 incorporated in the magnet structure 1, for example the NdFeB magnet used in Example 1, has a coercive force of 11 kOe to 12 kOe. In order to magnetize this NeFeB magnet, it is necessary to apply a magnetic field at least equal to or greater than the coercive force, and applying a magnetic field that is too high is unnecessary and difficult in terms of equipment. Therefore, in the case of a coercive force of 11 kOe, a magnetic field of 1.1 T to 3.6 T is usually applied. The coercive force iHc of the NdFeB magnet used in the magnet structure of the magnetic attachment for dentures is 10 kOe to 20 kOe, so a magnetic field of 2 T or more is sufficient for magnetization. However, due to equipment restrictions, it should be 4 T or less.

[0035] The inspection involves joining the attracting surface of the magnetic structure 101 and the attracted surface of the keeper 102 together, and measuring the tensile strength in the vertical direction with a tensile tester to determine the magnetic attracting force. The magnetic attraction force can be 800gf to 1000gf.

[0036] <Fall prevention test> Finally, a fall-off prevention test was conducted. The test method was to embed the magnetic structure 10 of the present invention, which corresponds to the magnetic structure 5, in a temporary denture made of resin, which corresponds to the denture base 63 shown in Fig. 11, and to prepare a tensile jig for fixing the magnetic structure 10. The temporary denture and the tensile jig were pulled by a tensile tester to determine their tensile strength. By providing the flange 11 to the cap 1 of the present invention, the tensile strength of the magnet structure with a diameter of 4.0 mm and a height of 1.5 mm is 40 to 60 kgf, and by adding a surface treatment, it is 60 kgf to 75 kgf. For comparison, without the flange and surface treatment, it was 15 kgf to 25 kgf. EXAMPLES

[0037] [Example 1] The magnetic attachment for a denture and the method for producing the same according to the present invention will be described with reference to FIGS. As shown in Figure 1, the magnetic attachment 10 for dentures in this example is a magnetic structure 101 consisting of a permanent magnet 2, a cap 1 with a flange 11 which is a container for storing the permanent magnet 2, and a shield plate 3 which serves as a lid for the recess opening of the cap 1, together with a keeper 102.

[0038] The configuration of the magnetic structure 101 will be described. The permanent magnet 2 is an NdFeB magnet with a BHmax of 52 MGOe, a coercive force iHc of 11 kOe, and an Ms of 1.33 T. Its size is 3.0 mm in diameter and 0.8 mm in height, with R portions formed at the corners. The cap 1 is made of 18Cr-2Mo stainless steel, and has a coercive force Hc of 30 Oe and a saturation magnetic flux density Bs of 16 kG. Its size is 3.8 mm in diameter and 1.3 mm in height.

[0039] The manufacturing method is to cut a 0.3 mm thick 18Cr-2Mo stainless steel plate into a disk shape with a diameter of 6.4 mm. Then, the material is drawn and extruded into a cylindrical shape with a diameter of 3.8 mm and a height of 1.3 mm. The container is made of The cap 1 has a flange 11 on the side of the upper end surface thereof, the flange 11 having a rounded projection of 0.25 mm. The height of the flange 11 was 0.25 mm, which was the same as the thickness of the bottom of the cylindrical container.

[0040] The shield plate 3 is disk-shaped, with the outer periphery being non-magnetic 32 and the rest being made of 18Cr-8Ni stainless steel magnet 31. The 18Cr-8Ni stainless steel magnet 31 has a fibrous structure in the thickness direction and is magnetized in that direction, with a saturation magnetization of 8,500 G, a coercive force of 150 Oe, an anisotropic magnetic field of 860 G and a residual magnetism of 6,400 G. The 18Cr-8Ni stainless steel magnet 3 and the permanent magnet 2 housed in the cap 1 form a composite magnet, achieving a large magnetic attraction force. At the same time, the shield plate 3 is welded to the boundary with the cap to protect the NdFeB magnet 2 from saliva in the mouth and other fluids, thus protecting it from corrosion. Furthermore, the non-magnetic part of the shield plate 3 magnetically isolates the composite magnet from the cap 1, preventing a decrease in the magnetic attraction force.

[0041] The NdFeB magnet 2 is inserted into the cap 1, and then the composite shield plate that serves as the lid is pressed into the recessed opening of the cap 1, and the surface side of the joint between the 18Cr-2Mo magnetic stainless steel cap 1 and the ring-shaped 18Cr-8Ni stainless steel 32 of the composite shield plate is laser welded. The weld 33 has a width of 0.3 mm and a depth of 0.08 mm. The magnet structure 101 was magnetized by applying a magnetic field of 2.5 T.

[0042] Next, the keeper 102 is made of 18Cr-2Mo stainless steel, and has a coercive force of 11 kOe and a saturation magnetic flux density Bs of 16 kG.

[0043] A comparative test of magnetic attraction was conducted between a denture magnetic attachment consisting of a Cr-Ni stainless steel magnet and a flanged cap made of Cr-based magnetic stainless steel of the present invention, and a conventional denture magnetic attachment consisting of a soft magnetic stainless steel cap and seal plate. Both have the same size and permanent magnet, and the only difference is whether they are magnet type or soft magnetic stainless steel type. As a result, the magnetic adhesion force of the magnetic attachment for dentures of the present invention was 920 gf, which is a 53% improvement compared to 600 gf for conventional magnetic attachments for dentures. In addition, in the drop prevention test, the tensile strength was 55kgf, a significant improvement over the conventional product's 23kgf.

[0044] [Example 2] In Example 1, assembly and laser welding were performed using a shield plate instead of the composite shield plate. The characteristics were equivalent to those of Example 1.

[0045] The cap 1 of Example 2 was subjected to a surface treatment. 70μm alumina powder is ejected at a pressure of 4kgf / mm 2 The specimen was shot blasted for 10 seconds at 1000K. The specimen was then immersed in a metal adhesive to a thickness of 12μm, and cured by natural drying. As a result, in the drop prevention test, the tensile strength was improved to 62 kgf. [Industrial Applicability]

[0046] By using a composite magnet, this invention enables a magnetic attachment for dentures to have a magnetic attraction force that is more than 1.4 times stronger than conventional products, and can be used without falling off the dentures, and is expected to become widely used. [Explanation of symbols]

[0047] 10: Magnetic attachment 101: Magnet structure 102;Keeper 1; Cap (Flanged Cap) 2; Permanent magnet 3;Shield plate 31: Cr-Ni stainless steel magnet (except for outer periphery) 32: Non-magnetic part (outer periphery) of Cr-Ni stainless steel 33: Welding 301; Semi-hard magnetic material 311;Shield Plate 312;Composite shield plate 11; Cap (Flanged Cap) 12; Permanent magnet 131; Semi-hard magnetic material (shield plate) 131a; Welded part (solidified part) 131b; Heat affected zone (non-magnetic zone)

Claims

1. A magnetic attachment for dentures comprising a magnetic structure to be placed on a denture and a keeper made of a soft magnetic material to be placed on an abutment tooth, the magnetic structure and the keeper being configured so that an attracting surface of the magnetic structure and an attractable surface of the keeper are brought into contact with each other by self-attraction caused by magnetic force, the magnetic structure has a cup-like shape with an opening, and the bottom and side portions of the magnetic structure are made of a cap made of Cr-based magnetic stainless steel, a permanent magnet housed in a recess of the cap, and a shield plate that covers the opening of the cap; The magnet structure has a cylindrical shape with a diameter of 1.5 mm to 5 mm and a height of 0.8 mm to 2 mm, The permanent magnet is formed in a disk shape having a maximum energy product of 45 MGOe to 55 MGOe, a coercive force of 10 kOe to 20 kOe, a thickness of 0.5 mm to 1.6 mm, and an outer diameter of 1.2 mm to 4.6 mm, the cap has a flange portion consisting of a protrusion of 0.1 mm to 0.25 mm on a side surface of an upper end side not in contact with the keeper, the side surface portion is made of a parallel fibrous structure along the side surface, and has a hardness of Hv220 to Hv300; The flange portion has an R-shaped inclined surface that slopes downward toward the upper end of the cap and is made of a semicircular arc-shaped fiber structure. the shield plate has an outer periphery made of non-magnetic Cr-Ni stainless steel, and the rest of the outer periphery is made of a Cr-Ni stainless steel magnet having a fibrous structure in the thickness direction; The Cr-Ni stainless steel magnet has magnetic properties in a saturated magnetized state, including a saturation magnetization of 8,000 to 12,000 G, a coercive force of 100 Oe to 200 Oe, an anisotropic magnetic field of 800 G or more, and a residual magnetization of 6,000 G to 10,000 G, The boundary between the end of the cap side surface and the shield plate is joined by welding. The suction surface, including the welded area, is smoothed. The magnetic attachment for dentures is characterized in that the keeper is disk-shaped, made of Cr-based soft magnetic stainless steel, and has a smoothed adsorption surface.

2. In claim 1, A magnetic attachment for dentures, characterized in that the outer peripheral side surface of the cap has a spiky uneven surface consisting of triangular pyramidal peaks with approximately the same depth and width, and a metal adhesive coating having a thickness of 20 μm or less.

3. 3. A method for manufacturing a magnetic structure for a denture magnetic attachment according to claim 2, comprising the steps of: (1) First, in the manufacture of the three components constituting the magnet structure, namely, a cap having a flange on the upper side made of Cr-based magnetic stainless steel, a permanent magnet made of a disk-shaped rare earth sintered magnet, and a shield plate which is a base material for the shield plate made of a disk-shaped stainless steel magnet, Step a) The cap is formed by punching a Cr-based magnetic stainless steel plate as a base material into a disk shape by cold working; Step b) Next, a cap is formed by backward extrusion press processing, and a protrusion of 0.1 mm to 0.25 mm is protruded from the side surface of the upper end of the cap, and a fibrous structure is formed along the shape of the protrusion, the protrusion having an R-shaped inclined surface descending outward on the upper end of the cap; Step c) further comprises flattening a lower surface of the protrusion to form a flange portion by forward extrusion press processing, the flange portion having a semicircular arc-shaped fiber structure; In addition, by performing the backward extrusion press process and the forward extrusion press process, the side surface of the cap is made of a parallel fibrous structure along the side surface, The hardness is Hv220 to Hv300. Step d) the shield plate is made of a Cr-Ni non-magnetic stainless steel as a base material, which is cold drawn by 50% or more, and induced to transform 60% or more of the austenite structure into martensite, and then machined into a ring shape to form a shield plate having a thickness of 0.1 mm to 0.2 mm and an outer diameter of 1.2 mm to 4.6 mm. The outer periphery of this shield plate is laser heated to be non-magnetically modified to return it to the Cr-Ni non-magnetic stainless steel consisting of the austenite phase, thereby forming a composite shield plate in which the center of the disk is made of stainless steel magnetic material and the outer periphery is non-magnetic; Step e) The permanent magnet is formed into a disk shape having a maximum energy product of 45 MGOe to 55 MGOe, a coercive force of 10 kOe to 20 kOe, a thickness of 0.5 mm to 1.6 mm, and an outer diameter of 1.2 mm to 4.6 mm; (2) Next, in assembling the magnetic structure consisting of the three parts of the cap, the composite shield plate, and the permanent magnet, Step f) inserting the permanent magnet into the hole of the cap, covering it with the composite shield plate, and assembling the three parts; Step g) laser welding the boundary between the cap and the composite shield plate; (3) Then, in the surface treatment, magnetization, and inspection of the assembled magnetic structure, Step h) shot blasting the magnet structure, coating it with dental metal adhesive, and curing it; Step i) polishing the attraction surface of the magnetic structure to make it smooth; Step j) applying a magnetic field of 2 T or more in a height direction to magnetize the magnetic structure; Step k) inspecting the attraction between the magnet structure and the keeper; 4. A method for manufacturing a magnetic structure utilizing a composite shield plate comprising the steps of:

4. A method for manufacturing a magnetic structure for a denture magnetic attachment, comprising the steps of: (1) First, in the manufacture of the three components constituting the magnet structure, a cap having a flange on the upper side made of Cr-based magnetic stainless steel, a permanent magnet made of a disk-shaped rare earth sintered magnet, and a shield plate which is the base material of the disk-shaped stainless steel magnet, Step a) The cap is formed by punching a Cr-based magnetic stainless steel plate as a base material into a disk shape by cold working; Step b) Next, a cap is formed by backward extrusion press processing, and a protrusion of 0.1 mm to 0.25 mm is protruded from the side surface of the upper end of the cap, and a fibrous structure is formed along the shape of the protrusion, the protrusion having an R-shaped inclined surface descending outward on the upper end of the cap; Step c) further comprises flattening a lower surface of the protrusion to form a flange portion by forward extrusion press processing, the flange portion having a semicircular arc-shaped fiber structure; In addition, by performing the backward extrusion press process and the forward extrusion press process, the side surface of the cap is made of a parallel fibrous structure along the side surface, The hardness is Hv220 to Hv300. Step d) The shield plate is made of a Cr-Ni non-magnetic stainless steel as a base material, which is cold drawn by 50% or more, and induced transformation of 60% or more of the austenite structure into martensite is performed. The base material is then machined into ring slices to form a shield plate made of a stainless steel magnet material in a disk shape having a thickness of 0.1 mm to 0.2 mm and an outer diameter of 1.2 mm to 4.6 mm; Step e) The permanent magnet is formed into a disk shape having a maximum energy product of 45 MGOe to 55 MGOe, a coercive force of 10 kOe to 20 kOe, a thickness of 0.5 mm to 1.6 mm, and an outer diameter of 1.2 mm to 4.6 mm; (2) Next, in assembling the magnetic structure consisting of the three parts of the cap, the shield plate, and the permanent magnet, Step f) inserting the permanent magnet into the hole of the cap, covering it with the shield plate, and assembling the three parts; step g) laser welding the boundary between the cap and the shield plate, and modifying the laser welding heat-affected zone on the shield plate side to be nonmagnetic to form a nonmagnetic portion at the boundary; (3) Then, in the surface treatment, magnetization, and inspection of the assembled magnetic structure, Step h) shot blasting the magnet structure, applying a metal adhesive thereto, and curing the same; Step i) polishing the attraction surface of the magnetic structure to make it smooth; Step j) applying a magnetic field of 2 T or more in a height direction to magnetize the magnetic structure; Step k) inspecting the attraction between the magnet structure and the keeper; A manufacturing method for a magnet structure characterized by a laser welding non-magnetic modification technology comprising the steps of:

Citation Information

Patent Citations

  • Permanent magnet assemble body for stabilizing artificial tooth

    JP1992227253A

  • Denture attachment

    JP1998127664A

  • Denture attachment, method for fixing the same, and spacer for fixing

    JP1998323356A

  • Manufacturing method of magnetic structural body with Anti-drop resin layer

    JP2001112791A

  • Denture attachment

    JP2011224109A